Cytokines profile changers after magnetic-heat-vibromassage in chronic abacterial prostatitis with erectile disfunction - D. G. Коren’kov; V. E. Marusanov (Андрология и генитальная хирургия, 2016)
The aim of the study was to examine the influence of magnetic-heat-vibromassage procedure in treatment of 27 patients with chronic abacterial prostatitis with erectile dysfunction, by mean of transrectal electrodes application of MAVIT® apparatus (ULP-01-“ELAT”). In the prostatic gland (PG) media and blood plasma the pro-inflammatory cytokine concentrations was investigated. PG hemodynamic, and erectile dysfunction also was determined. Control group was presented by 10 healthy males (23–45 years old). Measurements were done before treatment, and after 10 procedures of PG massage, and 30 days after procedure.It was shown that chronic abacterial prostatitis with erectile dysfunction with low clinical performance is supported by pro-inflammatory cytokines produced by the PG. The usage of magnetic-heat-vibromassage procedure increased prostatic microcirculation, as well as testosterone level, and improved the erectile dysfunction in all 27 patients enrolled into the study